Laser-induced graphene / MoS2 / Au composite material as well as preparation method and application thereof

Through the preparation of laser -induced graphene/MOS2/AU composite materials, the problems of high temperature operation, high power consumption, and complicated preparation methods of existing NO2 detection technology have been solved, and efficient and accurate NO2 testing has been achieved. Potential applications in the field.

CN119349565AActive Publication Date: 2025-01-24RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411458377.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing NO2 detection technology has problems such as high temperature operation, large power consumption, and complex preparation methods, making it difficult to achieve efficient and accurate detection of toxic gases.

Method used

The laser -induced graphene/MOS2/AU composite material is used to prepare high -efficiency gas -sensitive sensors through laser etching and chemical modification methods to achieve synchronous origin modification of MOS2 and AU.

Benefits of technology

The NO2 was performed efficient and sensitive to detect NO2 at nearly room temperature, avoiding the use of high -temperature and high -pressure conditions in traditional methods and the use of toxic chemicals, and reduced preparation costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349565A_ABST
    Figure CN119349565A_ABST
Patent Text Reader

Abstract

The invention provides a laser-induced graphene / MoS2 / Au composite material and a preparation method and application thereof.The preparation method comprises two times of laser engraving, so that MoS2 and Au modified laser-induced graphene is formed on a polyimide film, the material preparation method is rapid, economical and efficient, and synchronous in-situ modification of Au and MoS2 in a laser-induced graphene sensing area can be achieved. According to the invention, severe conditions of high temperature and high pressure and toxic chemicals involved in a traditional preparation mode are avoided, and the laser-induced graphene / MoS2 / Au can be used as a gas sensor to efficiently and sensitively detect toxic gases, and has potential application in the fields of environmental monitoring and biomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of poisonous gas detection, and in particular relates to a laser-induced graphene / MoS2 / Au composite material and a preparation method and application thereof. Background Art

[0002] NO2 is a reddish-brown acidic gas with a pungent odor. It can cause secondary pollution of the atmosphere, reduce atmospheric visibility, acidify surface water, and even cause acid rain and other environmental problems. NO2 can also pose a serious threat to human health. Short-term exposure to high-concentration NO2 vapor can cause acute poisoning, and long-term exposure to low-concentration NO2 can cause chronic poisoning, resulting in retardation, insomnia, multiple neuritis, atherosclerosis and other diseases. Based on the above problems, real-time and accurate detection of NO2 is of great significance to the fields of environmental protection and medicine, and also puts forward higher requirements for related NO2 detection technologies.

[0003] Existing NO2 detection methods mainly include laser spectroscopy, infrared spectroscopy, Raman spectroscopy, ion mobility spectroscopy, mass spectrometry, surface acoustic wave sensors, chromatography and semiconductor gas sensors. Among them, metal oxide semiconductor gas sensors have been widely studied due to their simple structure, low cost, long life and high sensitivity. However, they also have many shortcomings, usually need to operate at high temperatures, consume large power and have complex preparation methods.

[0004] The inherent huge specific surface area of ​​graphene materials and the defects and dangling bonds on the surface of the materials will provide a large number of adsorption sites for the gas molecules to be detected, reducing the activation energy required for the adsorption of gas molecules, thereby achieving the purpose of improving the response sensitivity and effectively reducing the detection temperature. However, the sensitivity of single graphene-based gas sensors is still far from practical applications, and the response / recovery time is long. Composite or functional modification of graphene with other materials can further improve its gas sensing performance. MoS2 has attracted widespread attention due to its rich active sites, selective adsorption of NO2 and inherent semiconductor properties. Composite MoS2 with graphene to form a pn heterojunction can increase the carrier density of the composite material at near room temperature and optimize the gas-sensitive response. In addition, noble metals can act as electron traps to suppress the recombination of electrons and holes, further increase the carrier concentration, and thus optimize the sensitivity of gas sensors. However, the current methods for preparing graphene are usually complicated, and the environmental and economic costs are high. Further modification requires additional experimental steps, and finally it needs to be attached to the interdigitated electrodes and installed with heating electrodes to reach the operating temperature. Therefore, there is an urgent need to develop an efficient, economical, and environmentally friendly preparation method for graphene-based composites and apply them to gas sensing. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] The present invention proposes a laser-induced graphene / MoS2 / Au composite material and a preparation method and application thereof, so as to solve the technical problem of efficient and accurate detection of toxic gases.

[0007] (II) Technical solution

[0008] In order to solve the above technical problems, the present invention proposes a method for preparing a laser-induced graphene / MoS2 / Au composite material, which comprises the following steps:

[0009] S1. Fixing the carbon precursor material on a glass plate, then washing and drying at room temperature;

[0010] S2. Draw a sensor pattern using drawing software, import the pattern into the laser, form a laser-induced graphene area on the carbon precursor material by laser etching, rinse with ultrapure water and dry at room temperature;

[0011] S3. Add MoS2 source precursor solution and Au source precursor solution to the laser-induced graphene area, and perform secondary laser etching after drying, so that the precursor solution decomposes and reacts to generate MoS2 and Au and deposits them on the surface of the laser-induced graphene area. Finally, use ultrapure water and anhydrous ethanol to clean and dry at room temperature to obtain laser-induced graphene / MoS2 / Au composite material.

[0012] Furthermore, in step S1, the carbon precursor material is a polyimide film.

[0013] Furthermore, in step S2, the drawing software is CorelDRAW.

[0014] Furthermore, in step S2, the shape of the etched area is dumbbell-shaped, and the area of ​​the etched area is not greater than 5 mm 2 .

[0015] Furthermore, in step S2, the laser is a CO2 laser, the etching adopts a grating mode, the etching power is 3.6 to 4.5 W, and the scanning speed is 120 to 180 mm / s.

[0016] Furthermore, in step S3, the solute of the Au source precursor solution is one of HAuCl4, HAuCl4·3H2O, and HAuCl4·4H2O, the solvent is ultrapure water, and the solution concentration is 0.05 to 0.5 mol L -1 .

[0017] Further, in step S3, the solute of the MoS2 precursor solution is a soluble molybdenum salt and a sulfur-containing compound, and the solvent is ultrapure water; the soluble molybdenum salt is (NH4)6Mo7O 24 .4H2O、(NH4)6Mo7O 24, Na2MoO4, Li2MoO4, and the sulfur-containing compound is CH4N2S or sulfur powder.

[0018] Furthermore, in step S3, the etching power of the laser secondary etching is 1.0-2.4 W, and the scanning speed is 25-70 mm / s.

[0019] In addition, the present invention also proposes a laser-induced graphene / MoS2 / Au composite material, which is prepared by the above method.

[0020] In addition, the present invention also proposes an application of a laser-induced graphene / MoS2 / Au composite material, and the laser-induced graphene / MoS2 / Au composite material is prepared into a gas sensor for the detection of chemical toxic gases.

[0021] (III) Beneficial effects

[0022] The present invention provides a laser-induced graphene / MoS2 / Au composite material and its preparation method and application. The preparation method includes two laser engravings to form laser-induced graphene modified with MoS2 and Au on a polyimide film. The material preparation method is fast, economical and efficient, and can achieve simultaneous in-situ modification of Au and MoS2 in the laser-induced graphene sensing area. The present invention avoids the harsh conditions of high temperature and high pressure and toxic chemicals involved in traditional preparation methods. Laser-induced graphene / MoS2 / Au can be used as a gas sensor to efficiently and sensitively detect toxic gases, and has potential applications in environmental monitoring and biomedical fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the preparation of laser-induced graphene / MoS2 / Au (LIG / MoS2 / Au) gas sensor;

[0024] Figure 2 XRD pattern of LIG / MoS2 / Au;

[0025] Figure 3a and 3b SEM images of LIG and LIG / MoS2 / Au, respectively, with a scale of 500 nm;

[0026] Figure 4a AFM images of LIG / MoS2 / Au, with scales of 400nm, Figure 4b is the corresponding cross-sectional profile curve;

[0027] Figure 5a and 5b TEM and HRTEM images of LIG / MoS2 / Au, with scales of 50nm and 5nm, respectively;

[0028] Figure 6a is the XPS spectrum of LIG / MoS2 / Au, Figure 6b is the C1s spectrum, Figure 6c is the Mo 3d spectrum, Figure 6d is the S2p spectrum, Figure 6e is the Au4f spectrum;

[0029] Figure 7 The response curves of LIG / MoS2 / Au, LIG / MoS2, LIG / Au, and LIG gas sensors to 1 ppm NO2 at 90 °C are shown in Table 1. The response value is defined as ΔR / R0 (ΔR = R a -R NO2 , R NO2 is the resistance of the sensor in NO2, R a is the resistance of the sensor in air);

[0030] Figure 8 The response curve of LIG / MoS2 / Au to 1ppmNO2 prepared at different secondary powers, the test temperature is 90℃;

[0031] Fig. 9 This is a statistical graph of the response values ​​of LIG / MoS2 / Au prepared with different concentrations of HAuCl4 as the Au source to 1ppmNO2. The test temperature is 90℃. DETAILED DESCRIPTION

[0032] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.

[0033] This embodiment provides a method for preparing a laser-induced graphene / MoS2 / Au composite material, which specifically includes the following steps:

[0034] S1. Place a 170 μm thick polyimide (PI) film tape (area: 1.5 × 1.5 cm 2 ) is pasted on a glass plate, then repeatedly cleaned with anhydrous ethanol and dried at room temperature;

[0035] S2. Draw a dumbbell-shaped pattern with the help of CorelDRAW drawing software, and import the pattern file into a commercial CO2 laser (wavelength 10.6μm); in air, the CO2 laser uses a grating mode to perform the first etching on the PI film tape in step S1 to form a laser-induced graphene (LIG) area; the etching area consists of two rectangles and a single line, and the area of ​​the single line area is 0.24×8mm 2 , as the sensing area, the rectangular area at both ends is 1.5×2mm 2, used to connect with copper foil, such as Figure 1 As shown; the laser parameters used are: scanning speed of 130 mm / s, etching power of 3.7 W, and pixel density of 1000 PPI;

[0036] S3. 0.35mmol (NH4)6Mo7O 24 ·4H2O and 15mmol CH4N2S were dissolved in 5mL ultrapure water to prepare a MoS2 precursor solution; 0.197g HAuCl4·3H2O was dissolved in 5mL ultrapure water to prepare a 0.1mol L -1 Au source precursor solution; add 0.004 mL of MoS2 precursor solution to the dumbbell-shaped line area of ​​laser-induced graphene, add 0.004 mL of Au source precursor solution after natural drying, and then place in a 60°C constant temperature forced air drying oven for 10 min to obtain a precursor;

[0037] The S4.CO2 laser was used in grating mode to perform a second laser etching on the dumbbell-shaped line area of ​​the laser-induced graphene with the precursor. The laser parameters used were: scanning speed 65 mm / s, scanning power 1.2 W, pixel density 1000 PPI; after laser heating, (NH4)6Mo7O 24 .4H2O and CH4N2S react to generate MoS2, HAuCl4 decomposes to generate Au and simultaneously attaches to the LIG line area; the dumbbell-shaped area is cleaned and dried with ultrapure water and ethanol to obtain a LIG / MoS2 / Au composite material.

[0038] A gas sensor is made based on the LIG / MoS2 / Au composite material. Conductive silver paste is coated on the square contact pads on both sides of the dumbbell-shaped LIG / MoS2 / Au to form two contact points. Two copper foils are used as wires and connected to the two contact points to form a gas sensor.

[0039] XRD characterization of LIG / MoS2 / Au. Figure 2 This is the XRD spectrum of LIG / MoS2 / Au. The characteristic peaks of graphene, Au and MoS2 appear simultaneously in the spectrum, confirming the successful preparation of LIG / MoS2 / Au.

[0040] SEM, AFM and TEM characterization of LIG / MoS2 / Au: Figure 3a and 3b These are the SEM images of LIG and LIG / MoS2 / Au, respectively. LIG presents a three-dimensional honeycomb structure, which is composed of stacked sheets. After Au and MoS2 are loaded, the LIG sheet becomes thicker. Figure 4a and 4bThe AFM images of LIG / MoS2 / Au and the corresponding cross-sectional profile curves respectively indicate that the thickness of the LIG / MoS2 / Au sheet is about 35 nm. Figure 5a As shown in the TEM image of LIG / MoS2 / Au, MoS2 and Au are dispersed on the LIG surface in the form of flake structures and nanoparticles, respectively. The HRTEM image of LIG / MoS2 / Au ( Figure 5b ) corresponds to the (111) plane of Au, the (002) plane of MoS2 and the (110) plane of LIG, respectively.

[0041] XPS characterization of LIG / MoS2 / Au: Mo, S, Au and C signals appear in the XPS total spectrum of LIG / MoS2 / Au ( Figure 6a ); Figure 6b The C1s spectrum of LIG / MoS2 / Au was fitted into five characteristic peaks, corresponding to sp 2 Hybridized carbon (284.4 eV), sp 3 Hybridized carbon (285.2V), CS (286.4eV), C=O (288.6eV) and satellite peaks (291.7eV), among which the peak at 284.4eV and the satellite peak at 291.7eV are the signature peaks of graphene structure (Adv. Mater., 2018, 30, 170731), and the formation of CS bonds indicates that there is a strong interaction between MoS2 and C (Adv. Energy Mater., 2019, 9, 1802553); Figure 6c This is the high-resolution XPS spectrum of Mo3d. The two characteristic peaks at binding energies of 232.1eV and 229.0eV correspond to Mo 3d 3 / 2 and Mo 3d 5 / 2 The two peaks at 233.7 eV and 235.5 eV are related to the unsaturated sulfur ligand (MoS4 2- ) and slightly oxidized surface (MoO3) (Adv.EnergyMater., 2019, 9, 1802553), the small peak at 226.2eV corresponds to S2s in MoS2; Figure 6d This is the high-resolution XPS spectrum of S2p. The two characteristic peaks at the binding energies of 161.5 eV and 162.7 eV correspond to S2p respectively. 3 / 2 and S2p 1 / 2 , corresponding to the basal plane S of MoS2 2- Ligand, the peak at 164.4 eV corresponds to the bridging disulfide S2 on the edge of MoS2 2-ligands, which indicates that LIG / MoS2 / Au has sulfur defects; Au4f high-resolution XPS spectrum of LIG / MoS2 / Au ( Figure 6e ) show two characteristic peaks at binding energies of 84.4 eV and 88.1 eV, corresponding to Au4f 7 / 2 and Au4f 5 / 2 .

[0042] The gas-sensing performance of the above-mentioned LIG / MoS2 / Au was characterized: the two ends of the prepared sensor were connected to the positive and negative electrodes of the source meter (Keithley 2400) respectively; the voltage was set according to the temperature of the LIG sensing area measured by a thermal imaging camera (FLIR ONE PRO); first, the prepared sensor was fixed in the air chamber, and its resistance was stabilized in the air atmosphere, and then 1ppm NO2 gas was introduced into the air chamber. After the resistance of the sensor was stabilized again, air was introduced into the test chamber to desorb NO2 from the surface of LIG / MoS2 / Au; the response value was calculated based on the change in the resistance of LIG / MoS2 / Au before and after the introduction of NO2.

[0043] The response curves of LIG, LIG / Au, LIG / MoS2 and LIG / MoS2 / Au to 1ppmNO2 at 90℃ are shown in Figure 2. Figure 7 As shown, all curves have negative responses, indicating that all sensors exhibit p-type semiconductor characteristics. Compared with pure LIG, the response value of LIG / MoS2 / Au increases significantly; Figure 8 The response curves of LIG / MoS2 / Au obtained under different secondary laser powers. With the increase of laser power, the response value of LIG / MoS2 / Au sensor to 1ppmNO2 first increases and then decreases. When the laser power is 4%P0 (P0: total laser power), the response value is the largest. Fig. 9 The response curve of the sensor to 1ppmNO2 obtained by dropping different concentrations of HAuCl4 is shown. It is observed that the response value of the sensor first increases and then decreases with the increase of HAuCl4 concentration. When the concentration of HAuCl4 is 0.1M, the response value is the largest.

[0044] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a laser-induced graphene / MoS2 / Au composite material, characterized in that: The preparation method comprises the following steps: S1. Fixing the carbon precursor material on a glass plate, then washing and drying at room temperature; S2. Draw a sensor pattern using drawing software, import the pattern into the laser, form a laser-induced graphene area on the carbon precursor material by laser etching, rinse with ultrapure water and dry at room temperature; S3. Add MoS2 source precursor solution and Au source precursor solution to the laser-induced graphene area, and perform secondary laser etching after drying, so that the precursor solution decomposes and reacts to generate MoS2 and Au and deposits them on the surface of the laser-induced graphene area. Finally, use ultrapure water and anhydrous ethanol to clean and dry at room temperature to obtain laser-induced graphene / MoS2 / Au composite material.

2. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S1, the carbon precursor material is a polyimide film.

3. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S2, the drawing software is CorelDRAW.

4. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S2, the shape of the etched area is dumbbell-shaped, and the area of ​​the etched area is no larger than 5 mm 2 .

5. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S2, the laser is a CO2 laser, the etching is performed in grating mode, the etching power is 3.6-4.5W, and the scanning speed is 120-180mm / s.

6. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S3, the solute of the Au source precursor solution is one of HAuCl4, HAuCl4·3H2O, and HAuCl4·4H2O, the solvent is ultrapure water, and the solution concentration is 0.05 to 0.5 mol / L -1 .

7. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S3, the solute of the MoS2 precursor solution is a soluble molybdenum salt and a sulfur-containing compound, and the solvent is ultrapure water; the soluble molybdenum salt is (NH4)6Mo7O 24 .4H2O、(NH4)6Mo7O 24 , Na2MoO4, Li2MoO4, and the sulfur-containing compound is CH4N2S or sulfur powder.

8. The method for preparing the laser-induced graphene / MoS2 / Au composite material according to claim 1, characterized in that: In step S3, the etching power of the laser secondary etching is 1.0-2.4 W, and the scanning speed is 25-70 mm / s.

9. A laser-induced graphene / MoS2 / Au composite material, characterized in that: The laser-induced graphene / MoS2 / Au composite material is prepared by the method described in any one of claims 1 to 8.

10. An application of laser-induced graphene / MoS2 / Au composite material, characterized in that: The laser-induced graphene / MoS2 / Au composite material described in claim 9 is prepared into a gas sensor for detecting chemical toxic gases.

Citation Information

Patent Citations

  • Laser induced graphene materials and their use in electronic devices

    CN106232520A

  • Method for preparing single-layer multilayer graphene thermoelectric detector through laser ablation

    CN108963065A

  • Laser-induced porous graphene / Au material and preparation method and application thereof

    CN118083962A

  • Graphene-based gas sensing platform

    US20230003676A1